Teaching - Learning Situation of Speaking in English at the University Level: A Case Study - Hosain, Md Iqbal (IIUC Studies, 2012)
This paper intends to find out the problems that the students face in speaking in English at the different universities in Bangladesh. It investigates the merits and demerits of the existing teaching methodology of English at the university level. With a view to finding out the causes of the students lack of competence in speaking in English, some authentic data have been collected from the different universities of the country. And after a thorough analysis, a suggestion has been made for teachers to use some pragmatic ways of improving speaking skills in English. It further examines the different techniques of teaching speaking in English at the university level along with its curriculum and testing system, and offers some easy and modern methods of teaching English. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12267 IIUC Studies Vol.7 2011: 179-196